Justification of the problem of improving the organizational and managerial training of trainers on sports - Toni Khazim; Vladimir Paevskyy (Kharkiv State Academy of Physical Culture, 2014)
Purpose: justification ways to improve the professional activity of the future coaches in the new organizational and management conditions. Materials and methods: is used the theoretical analysis and compilation of references and documents that reflect the experience of physical culture and sports organizations. Results: in the present conditions the content of training future trainers reduced only to the formation of them as experts in the planning and implementation of the training process. Conclusion: the future trainers should receive sufficient organizational and management training, including in the field of project management in order to successfully fulfill the role of managers to ensure the organization of sports training.